The protective effect of PL 1-3 on D-galactose-induced aging mice - Li, Pengxiao; Ma, Yazhong; Wang, Xiaotong; Li, Xin; Wang, Xuekun; Yang, Jie; Liu, Guoyun (Frontiers in Pharmacology, 2024)
The aging population has become an issue that cannot be ignored, and research on aging is receiving increasing attention. PL 1-3 possesses diverse pharmacological properties including anti-oxidative stress, inhibits inflammatory responses and antiapoptosis. This study showed that PL 1-3 could protect mice, especially the brain, against the aging caused by D-galactose (D-gal). D-gal could cause oxidative stress, inflammation, apoptosis and tissue pathological injury and so on in aging mice. The treatment of PL 1-3 could increase the anti-oxidative stress ability in the serum, liver and brain of aging mice, via increasing the total antioxidant capacity and the levels of anti-oxidative defense enzymes (superoxide dismutase, glutathione peroxidase, and catalase), and reducing the end product of lipid peroxidation (malondialdehyde). In the brain, in addition to the enhanced anti-oxidative stress via upregulating the level of the nuclear factor erythroid 2-related factor 2 and heme oxygenase 1, PL 1-3 could improve the dysfunction of the cholinergic system via reducing the active of acetylcholinesterase so as to increase the level of acetylcholine, increase the anti-inflammatory and antiapoptosis activities via downregulating the expressions of pro-inflammatory cytokines (interleukin-6 and tumor necrosis factor-) and pro-apoptosis proteins (Bcl-2 associated X protein and Caspase-3) in the D-gal-induced aging mice, to enhance the anti-aging ability via upregulating the expression of sirtuin 1 and downregulating the expressions of p53, p21 and p16. Besides, PL 1-3 could reverse the liver, kidney and spleen damages induced by D-gal in aging mice. These results suggested that PL 1-3 may be developed as an anti-aging drug for the prevention and intervention of agerelated diseases.